Predictability of stock market prices - Granger, C. W. J.; Morgenstern, Oskar (Lexington, Mass. : Heath Lexington Books, 1970)
The book is the result of the authors' long-standing interest in stock market prices. The prices in 1961 were considered in connection with the development of particularly powerful techniques for analyzing economic time series known as spectral methods
Bibliography: p. [285]-296.
osc 24/07/2018
Loans
Keywords: Stock price forecasting; Random walks (Mathematics)